Unveiling intrinsic material and extrinsic pinning dimensionality in superconductors: Why Fe(Se,Te) is able to mimic YBCO - Gaia Grimaldi; Masood R. Khan; Antonio Leo; Mario Scuderi; Francesco Rizzo; Andrea Augieri; Giuseppe Celentano; Armando Galluzzi; Michela Iebole; Massimiliano Polichetti; Angela Nigro; Valeria Braccini (iScience, 2024)
Summary: Discovery of iron-based superconductors paved the way to a competitor of high-temperature superconductors, easier to produce, better performing in high fields, and promising to be less expensive. Critical parameters are investigated by resistivity measurements as a function of temperature, field, and angle R(T,H,θ). This work presents a deep analysis of H-θ phase diagram of PLD-processed Fe(Se,Te) superconducting films, thus revealing material and pinning anisotropy at once. By selecting different thresholds along the R(T,H,θ) curves, all possible regimes emerge. Surprisingly, anisotropy arises moving from the upper critical field toward the irreversibility line: gradually a non-monotonous transition from 3D to 2D, and backward to 3D occurs. Although Fe(Se,Te) appears as a 3D superconductor, its anisotropic pinning landscape shows up similarities with an intrinsic layered superconductor and Fe(Se,Te) definitively mimics YBCO. We propose a general method to disentangle, in any other superconductor, material dimensionality and pinning anisotropy that are key constraints for applications.